Análisis del impuesto de renta para las personas jurídicas del régimen ordinario para pymes bajo la Ley 2277 de 2022 reforma tributaria para la igualdad y la justicia social (2023)
Throughout the last two decades, the Colombian economy has undergone a series of changes in its tax system, which directly affects its political regime, which is why at least 13 tax reforms have been Carried out throughout the different administrations.